Local electrode atom probe tomography : a user's guide - Larson, David J.; Prosa, Ty J.; Ulfig, Robert M.; Geiser, Brian P.; Kelly, Thomas F. (Springer New York Imprint: Springer, 2013)
This book is the first, single-source guide to successful experiments using the local electrode atom probe (LEAP®) microscope. Coverage is both comprehensive and user friendly, including the fundamentals of preparing specimens for the microscope from a variety of materials, the details of the instrumentation used in data collection, the parameters under which optimal data are collected, the current methods of data reconstruction, and selected methods of data analysis. Tricks of the trade are described that are often learned only through trial and error, allowing users to succeed much more quickly in the challenging areas of specimen preparation and data collection. A closing chapter on applications presents selected, state-of-the-art results using the LEAP microscope. Written from the user perspective by the developers of the instrument themselves Covers the main features of a local electrode atom probe tomography experiment from start to finish Contains practical hints and tutorial information that is useful to any atom probe operator to improve the chances of a successful analysis Includes a chapter on hardware/instrumentation, which explains to the novice user the various parts of the instrument and how they operate Provides an overview of the software methods employed in LEAP, including reconstruction and data analysis